Visco-Elastic Characteristic of Bitumen Incorporating Nano Silica - Khairil Azman, Masri; Putra Jaya, Ramadhansyah; Mohamad, Idris Ali; Noram Irwan, Ramli; Haryati, Awang (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
Conventional asphalt binder usually has a few deficiencies such as poor deformation resistance especially under various temperature and heavy repetitive loads. To certify that problem, the properties of the asphalt binder will be improved by utilising polymers. But, the utilisation of polymer materials will lead to poor stability of specimens as well as reducing the resistance towards the ageing condition. Another promising material that is used for asphalt modification is nanomaterial such as nano-silica. Therefore, this study utilised nano silica as an asphalt modifier. This study emphasizes on the resistance enhancement of NS modified asphalt binder (NS-MB) towards repetitive stresses, various temperature and ageing conditions. The test involve was Multiple Stress Creep & Recovery (MSCR) evaluation using Dynamic Shear Rheometer (DSR). The results show that modified NS-MB produced a lower value of accumulated strain & non-recoverable creep compliance (Jnr) compared to unmodified NS-MB for various temperature and ageing conditions. The results also show that the addition of 2% NS produced the highest value of Recoverable Strain (R), thus it can be concluded that NS is capable in enhancing the visco-elastic behaviour of asphalt binder under repetitive loads.